Antidepressant Activity Study of Keruing (Dipterocarpus grandiflorus) Oleoresin Candle Aromatherapy on Male Mice (Mus musculus) Balb/C Strain - Agus, Adhe Septa Ryant; Butar-Butar, Maria Elvina Tresia; Fernandes, Andrian; Maharani, Rizki; Awan, Kevin Imanuel; Luhat, Martin Gilbert (Universitas Muhammadiyah Surabaya, 2024)
Depression represents a manifestation of prolonged stress, which, if left untreated, may lead to severe mental disorders. For depression treatment therapy, it can be carried out based on evidence-based treatment for depression and anxiety. Aromatherapy candles can be used as a non-pharmacological medium for depression therapy, where keruing has active compounds are phthalic acid di(3-methoxybenzyl) ester and phthalic acid, 5-ethyl-1,3-dioxan-5-yl octyl ester, causing keruing oleoresin to have a distinctive fragrance. This study aims to evaluate the pharmacological potential of keruing as an antidepressant for non-pharmacological therapy. Aromatherapy candles were formulated with keruing oleoresin at concentrations of 0%, 2.5%, 5%, 7.5%, and 10%, followed by testing their antidepressant activity using the Conditioned Place Preference (CPP) method. The results of the Paired T-test for groups F0, F2, and F4 or formulas containing 0%, 5%, and 10% of keruing oleoresin have a significant effect (sig. values <0.05) between pre and post-test being given aromatherapy and induction. In the One-way ANOVA test, between their groups, it can be seen there was no significant difference in test activity, namely for the pre-treatment test (sig. 0.445 > 0.05) and for the post-treatment test (sig. 0.065 > 0.05). Results indicated that while the candles met physical quality standards outlined by the Indonesian National Standard (SNI), no significant antidepressant effects were observed in mice. Further refinement in methodology, including the concentration of active compounds and delivery methods, is recommended to enhance the pharmacological potential of keruing oleoresin.